The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1590/s1517-83822013000400028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of virulence genes in strains of Campylobacter jejuni isolated from human, bovine and broiler

Abstract: Campylobacter jejuni isolates of different origins (bovine, broiler meat, human) were screened by polymerase chain reaction for the presence of 4 genes cdtB, cst-II, ggt, and virB11, previously linked to virulence such as adherence, invasion, colonization, molecular mimicry, and cytotoxin production. In addition, the isolates were screened for the presence of the global gene regulator csrA linked to oxidative stress responses, biofilms formation, and cell adhesion. All the C. jejuni isolates were positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
26
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
7
26
3
5
Order By: Relevance
“…Previous studies reported a high prevalence of pld A gene in Campylobacter isolates such as 100% for pld A gene was reported by Frazão et al, . Relatively low prevalence (11.25%) of vir B11 gene was found in C. jejuni which was in accordance with previous reports (González‐Hein, Huaracán, García, & Figueroa, ; Wieczorek, Szewczyk, & Osek, ).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported a high prevalence of pld A gene in Campylobacter isolates such as 100% for pld A gene was reported by Frazão et al, . Relatively low prevalence (11.25%) of vir B11 gene was found in C. jejuni which was in accordance with previous reports (González‐Hein, Huaracán, García, & Figueroa, ; Wieczorek, Szewczyk, & Osek, ).…”
Section: Discussionsupporting
confidence: 90%
“…The occurrence of the virB11 gene was a marker for the plasmid pVir, which is associated with invasiveness. It should be noted that the distribution pattern of virB11 in the C. jejuni isolates was 3/25 (12%) which was higher than that determined by González-Hein et al (2013) and closely similar to the findings of Van Deun et al (2013). Concerning the existence of cytotoxin genes, our study confirmed that cdtA was present in all the C. jejuni isolates, confirming the widespread of cytotoxin genes in poultry isolates as demonstrated by Rozynek et al (2005) and Van Deun et al (2007).…”
Section: Discussionsupporting
confidence: 89%
“…These authors point out that the lack of cytotoxicity found among strains with pathogenicity determinants may result from low toxin production. According to Jain et al (2008) and Gonzalez-Hein et al (2014), this is CdtB cytotoxin subunit encoded by cdtB gene that plays an essential role in exerting a toxic effect on cells. This is reflected by own studies, which reported no cytotoxic effect of the cell-free supernatants of three C. jejuni isolates from cattle and having only cdtA and cdtC genes.…”
Section: Discussionmentioning
confidence: 99%